2010
DOI: 10.1080/0972060x.2010.10643840
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oils of the Aerial Parts of TwoHypericum (H. pseudolaeveRobson andH. thymbrifoliumBoiss. & Noë) (Guttiferae) Species from Turkey

Abstract: In this study, essential oil composition of two Hypericum L. (Hypericum pseudolaeve Robson and H. thymbrifolium Boiss. & Noë ) species grown in Turkey were determined by using GC and GC-MS system. The essential oils obtained by hydrodistillation from the aerial parts of plants. Forty-five compounds were identified in the essential oils of H. pseudolaeve; transcaryophyllene (23.92 %), δ-limonene (11.19 %), α-cadinol (10.67 %), caryophyllene oxide (7.96 %), α-pinene (5.76 %), spathulenol (5.21 %) and β-selinene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The chemical analysis results of O. siifolius showed that this species may be a different group and could be transferred to a genus different from Crenosciadium. As in our previous studies, the chemical analysis results supported the morphological data [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…The chemical analysis results of O. siifolius showed that this species may be a different group and could be transferred to a genus different from Crenosciadium. As in our previous studies, the chemical analysis results supported the morphological data [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…capitatum and var. luteum [8], H. thymbrifolium and H. pseudolaeve [6], H. avicularifolium subsp. depilatum var.…”
Section: Gas Chromatography/mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…Hypericum species have been reported to contain many bioactive compounds, namely naphthodianthrones, phloroglucinols, flavonoids, phenylpropanes, essential oils, amino acids, xanthones, tannins, procyanidins and other components, which possess a wide array of biological properties [2][3][4]. Major/high component of the Hypericum essential oils are 1-hexanal, α-pinene, pinene, 3-methylnonane, 3-methyldecane, caryophyllene oxide, spathulenol, germacrene D, camphor, limonene and trans-caryophyllene [5][6][7][8][9]. Variations in the essential oils composition of many species of this genus were previously reported, and depending on genetic and environmental factors, seasonal variation, plant organs and analytical methods used [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…var. elongatum (Ledeb) Woron [ 11 ]; tr -caryophyllene (23.92%), limonene (11.19%), and α-cadinol (10.67%), caryophyllene oxide for H. pseudolaeve Robson [ 12 ]; α-pinene (71.2%), caryophyllene oxide (2.9%), and caryophylladienol I (0.6%) for H. lydium [ 13 ]; and germacrene D (30.2%) and α-pinene (21.5%) for H. confertum Choisy [ 14 ] were determined to be the predominant compounds in the essential oils.…”
Section: Introductionmentioning
confidence: 99%